Reproductive Trends in Cebu Cattle Grazing Rice Crop Residues in Colombian Tropical Dry Forest (2013)
ABSTRACT: The objective of this study was to describe the trend of reproductive performance of primiparous and multiparous cows that grazed rice crop residues located in a Dry Tropical Forest of Colombia, taking into account the rainfall pattern of the place. In this study, 89 primiparous and 309 multiparous Cebu cattle records were analyzed. Mean, mean standard deviation for age at first calving and open days of primipar- ous Cebu cattle were 41.05 ± 1.85 months and 269.7 ± 36.25 days respectively. Confidence intervals (95%) for both reproductive parameters were 36.8 - 45.3 months and 202.7 - 336.6 days respectively. For multiparous Cebu cattle, the mean and mean standard deviation for open days and calving interval were 245.6 ± 36.8 days and 17.5 ± 0.9 months respectively. Confidence intervals 207.1 - 366.9 days and 13.9 - 20.7 months respectively. The mean rainfall since 1999 until 2012 was 1202 mm per year. The reproduc- tive trend of the primiparous cattle showed an increasing behavior of age at first calving since 1999 until 2012, that can possibly be explained due to the decreasing behavior of the rainfall throughout the years, that can affect the nutritional value and offer of the grass that can grow in the borders of the crop, such as Guinea and Star grass, and eventually affect the body condition and weight necessary to be ready for the first estrous. An inverse behavior of open days occurred, showing a decreased trend along the last years of research. This fact could have happened due to the intensive use of the enriched rice straw with urea and molasses lately. Regarding to the reproductive trend of the multiparous cattle, there is no an evident pat- tern of it. Factors such as rainfall, temperature, nutrition and management should have affected it. Furtherres earch on this topic is needed.